Identitas Etnis Buton dalam Pemilihan Gubernur Sulawesi Tenggara Tahun 2018: Kemenangan Kubu Ali Mazi - Lukman Abunawas di Kota Baubau Provinsi Sulawesi Tenggara - Nur, La Ode Muhammad Adam; Kamarudin, Kamarudin (Indonesian Democracy Research Center, 2022)
The general aim of this study is to find out the identity of the Butonese ethnicity in the 2018 Southeast Sulawesi Governor Election which specifically aims to find out the strategic efforts of the Ali Mazi - Lukman Abunawas camp in attracting Butonese ethnic sympathy in the 2018 Southeast Sulawesi Governor Election as well as to find out the factors which caused the Butonese to choose Ali Mazi - Lukman Abunawas in the election for the Governor of Southeast Sulawesi in 2018. The data analysis used was descriptive qualitative, namely analyzing data where the data was obtained from interviews and documentation which were then described in the form of descriptions. The results showed that the causes of Butonese ethnic support for Ali Mazi and Lukman Abunawas were influenced by sociological factors of Butonese voters as in making their choice, people in Southeast Sulawesi who were ethnic Butonese were still influenced by ethnic traditions and ethnic similarities. The victory of Ali Mazi, who incidentally is a native of Buton, is influenced by the Butonese ethnic community, which tends to vote based on having the same ethnicity or the same clan as them. The strategic efforts of the Ali Mazi – Lukman Abunawas camp in attracting Butonese ethnic sympathy in the 2018 Southeast Sulawesi Governor Election, namely by using Butonese ethnic language and symbols during the campaign period. The language derived from the Butonese ethnic group is a channel of communication for regional head candidates. Ethnic language becomes an instrument in making an emotional approach because there will be a feeling of belonging between the candidate and the community.